Ushering in a New Dawn : Demand-Side Local Flexibility Platform Governance and Design in the Finnish Energy Markets - Rahman, Nayeem; Rabetino, Rodrigo; Rajala, Arto; Partanen, Jukka (My University, 2021)
Energy ecosystems are under a significant transition. Local flexibility marketplaces (LFM) and platforms are argued to have significant potential in contributing to such a transition. The purpose of this study was to answer the following research question: how do market conditions and stakeholders shape emerging LFM platform governance choices? We approached this objective with an exploratory single-case study by conducting ten semi-structured interviews with key stakeholders in the Finnish energy ecosystem. The results of the content and pattern analyses revealed the key challenges to LFM implementation such as the current regulatory treatment of flexibility, high costs of gadget installations, and ensuring sufficient liquidity in the market. In addition, we also demonstrated that despite such barriers, the Finnish ecosystem is largely pragmatic about LFMs’ in its midst. All in all, we contributed to the non-technological streams of LFM literature by developing an exhaustive framework with four distinctive dimensions (i.e., ecosystem readiness, value-creation logic, platform architecture and governance, platform competitiveness) for LFM development, which helps academics, practitioners, and policy-makers to understand how novel platforms emerge and develop.
Keywords: flexibility; demand-side flexibility; local flexibility market; flexibility service; platforms; energy platform; platform governance and design; Finnish energy markets; fi=Markkinointi|en=Marketing|